2018
DOI: 10.1097/mcg.0000000000000937
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Early Versus Delayed Colonoscopy in Lower Gastrointestinal Bleeding Using a Hospital Administrative Database

Abstract: Early colonoscopy does not affect 30-day mortality but may allow for earlier endoscopic intervention and decreased transfusion need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
5
12
0
Order By: Relevance
“…This slight reduction in length of stay also was observed in prior studies examining the role of early colonoscopy in patients with acute LGIB. 11,12 These findings also were observed in a larger cross-sectional study using the Nationwide Inpatient Sample database. 13 Although the early colonoscopy group underwent fewer endoscopic interventions, it is plausible that this allowed identification of select low-risk patients in whom the initial diverticular bleed had resolved spontaneously and, thus, facilitated earlier discharge.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This slight reduction in length of stay also was observed in prior studies examining the role of early colonoscopy in patients with acute LGIB. 11,12 These findings also were observed in a larger cross-sectional study using the Nationwide Inpatient Sample database. 13 Although the early colonoscopy group underwent fewer endoscopic interventions, it is plausible that this allowed identification of select low-risk patients in whom the initial diverticular bleed had resolved spontaneously and, thus, facilitated earlier discharge.…”
Section: Discussionsupporting
confidence: 62%
“…This decreased intervention rate is different from the aforementioned studies, 11 as well as results from our previously published work. 12 There are a few potential explanations for this finding. First, the lack of interventions in early colonoscopy may be representative of real-world management of diverticular bleeding because our data set is a national representative sample.…”
Section: Discussionmentioning
confidence: 99%
“…Another RCT did not show any difference in clinical outcome with EC and it was prematurely terminated [10]. Similarly, observational studies [20,21] showed that EC provided no mortality benefit. Results from seven meta-analyses [28][29][30][31][32][33][34] have yielded mixed results, with four reporting no difference in diagnostic yield [28,30,32,34] while three report increased diagnostic yield [29,31,33]; all showed no difference in rebleeding rate; all reported no difference in LOS except one [29]; no difference in transfusion requirement but one reported increased transfusion for EC [33]; all showed no difference in mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…We report here that between 2005 and 2014, the number of patients admitted with LGIB has increased, but mortality among these patients is improving. In addition, despite guidelines and non-randomized data supporting that EC may lead to more rapid identification of colonic lesions 11 and shorter hospital LOS 15 20 21 22 23 , EC has not been widely adopted. Finally, in patients admitted with LGIB, EC was associated with decreased LOS and cost of hospitalization, but no significant difference in mortality compared to LC.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Similarly, in acute lower GI bleeding, early colonoscopy compared with elective one does not benefit in terms of rebleeding, hospital stay, and mortality. [26][27][28] In patient with acute cholangitis with varying severity, most of the patients respond to aggressive hydration and IV antibiotics, and 20-30% of patients with severe cholangitis require biliary drainage. 29 ERCP is the best method for biliary drainage in patients with acute cholangitis, and emergent ERCP within 48 hours reduces mortality, hospital stay and organ failures.…”
Section: Triaging Before Endoscopymentioning
confidence: 99%